Determination of the fatigue critical distance according to the Line and the Point Methods with rounded V-notched specimen. (January 2018) - Santus, C.; Taylor, D.; Benedetti, M.
Highlights: Critical distance determination with plain and rounded V-notched specimens. Analytical procedure for inverse search according to the Line and Point Methods. Dimensionless forms and available coefficients obtained with FE simulations. Definition of an accuracy range minimizing the experimental variation sensitivity. Sensitivity effect of the relative notch radius size to the critical distance. Abstract: The critical distance length should in principle be deduced from the plain specimen fatigue limit and the threshold stress intensity factor range. However, the threshold range is difficult to measure experimentally, hence this length is usually obtained by means of a notched specimen. The critical distance inverse search, both according to the Line and the Point Methods, is presented in this paper referring to a relatively sharp V-notched specimen. Precise indications about the geometry parameters are given along with a complete analytical procedure to easily obtain the critical distance. A sensitivity analysis is discussed, providing evidence of a critical distance range for a well-posed inversion problem.